The Position of The Honorary Council of The Constitutional Court in the Indonesian Legal Order - Juanda Juanda; Nanda Dwi Rizkia (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
ABSTRACT This research is qualitative research with a normative approach. The data that researchers use in this article is secondary data that researchers obtained from various credible sources such as legal regulations, books, articles, scientific and various other sources. The data that the researchers used were analyzed using three legal analysis techniques, namely normative legal analysis techniques, historical legal analysis techniques, and telelogical legal analysis techniques. The result in this article show The Honorary Council of the Constitutional Court has existed since the enactment of Law no. 24 of 2003, namely Article 23 paragraph (3), which states that; "Requests for dishonorable dismissal as intended in paragraph (2) letters b, c, d, f and g are made after the person concerned has been given the opportunity to defend himself before the Honorary Council of the Constitutional Court." Then in 2006 the Constitutional Court established a Regulation concerning the Honorary Council of the Constitutional Court, namely regulation Number 10/PMK/2006. Regarding changes to Law no. 24 of 2003, the Honorary Council was only defined after the enactment of Law no. 8 of 2011. Article 1 number 4 of Law no. 8 of 2011 states that: "The Honorary Council of the Constitutional Court is a device established by the Constitutional Court to monitor, examine and recommend actions against Constitutional Judges, who are suspected of violating the Code of Ethics and Code of Conduct for Constitutional Judges. Thus, the statement regarding the Honorary Assembly of the Constitutional Court only existing in 2023 is not justified.Theologically, the formation of the constitutional court has objectives, duties and authority, among others: 1. The Honorary Council has the authority to maintain the dignity and honor of the Court. 2. The Honorary Council has the authority to examine and decide on alleged violations of the Code of Ethics and Conduct of Constitutional Judges 3. Alleged violations of the Code of Ethics and Conduct of Constitutional Judges can be examined and decided within a maximum of 30 working days from the time the report is recorded in e-BRLTP 4. In terms of a period of 30 days If the inspection has not been completed, it can be extended for a maximum of 15 working days.